The influence of cooperative learning model types of teams games tournaments on students' critical thinking ability - Muttaqien, Arif Rahman; Suprijono, Agus; Purnomo, Nugroho Hari; Rendy A.P, Dwi Bagus (International Journal for Educational and Vocational Studies, 2021)
This study aims to determine the effect of the Teams Games Tournaments (TGT) learning model which has an impact on consistent changes in students' critical thinking skills in Social Science subjects. The study used a quantitative approach with a pretest-posttest control group design. The research sample was students of MTs N 4 Sidoarjo class VIII determined by the cluster proportional random sampling technique. The experimental class is taught using the TGT model and the control class is using the discussion learning model. Both research classes were measured critical thinking ability. The data obtained were tested using an Independent-sample t-test to see the difference in the two research classes to see the difference between the pretest and posttest of critical thinking skills. The results showed that there was a positive influence on students' critical thinking skills in using the TGT model. In the experimental class taught using the TGT learning model, their critical thinking skills were better than the discussion learning model. The final assessment shows that critical thinking skills show Sig. (2-tailed) 0.011 < 0.05, which means that there is a significant difference. The existence of a significant difference indicates that there is an effect of the TGT learning model on students' critical thinking skills.